2003
DOI: 10.1046/j.1365-2958.2003.03459.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel sRNA component of the carbon storage regulatory system of Escherichia coli

Abstract: Homologues of csrC are apparent in several Enterobacteriaceae. The regulatory and evolutionary implications of these findings are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
492
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 344 publications
(508 citation statements)
references
References 51 publications
16
492
0
Order By: Relevance
“…Normal transcription of both csrB and csrC depends on P-UvrY, although csrB transcription is more highly dependent than that of csrC (3,36,38). In addition, the RNA helicase DeaD activates UvrY translation, which then activates csrB/C transcription (62).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Normal transcription of both csrB and csrC depends on P-UvrY, although csrB transcription is more highly dependent than that of csrC (3,36,38). In addition, the RNA helicase DeaD activates UvrY translation, which then activates csrB/C transcription (62).…”
Section: Resultsmentioning
confidence: 99%
“…Although we were unable to detect expression of csrB or csrC using in vitro transcription reactions with purified components (data not shown), P-UvrY was previously found to directly activate the expression of csrB-lacZ and csrC-lacZ transcriptional fusions in S-30 transcription-translation assays (36,38). Thus, we used the latter approach to determine if cAMP-CRP directly represses expression from the csrC-lacZ transcriptional fusion in the plasmid pLFXcsrC-lacZ.…”
Section: Fig 2 Effects Of Camp-crp On Csrb and Csrc Levels And Decay mentioning
confidence: 91%
See 2 more Smart Citations
“…The remaining sRNAs function by protein sequestration. Examples of sRNAs identified that regulate by this mechanism include CsrB, CsrC and 6S RNA (Liu et al, 1997;Wassarman & Storz, 2000;Weilbacher et al, 2003).…”
Section: Introductionmentioning
confidence: 99%